2008
DOI: 10.3396/ijic.v4i1.005.08
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Antibiotic Decisions for Upper Respiratory Tract Infections I:A Survey of Family Physicians

Abstract: Identifying factors associated with the ubiquitous inappropriate prescribing of antibiotics for upper respiratory tract infections (URTIs) will help develop effective interventions and decrease antimicrobial resistance. Surveys were mailed to family physicians in Ontario, Canada. The survey assessed antibiotic prescribing for URTIs and a wide range of influences on antibiotic decisions. Multivariate models of inappropriate prescribing were generated. 316 of 544 (58%) family physicians completed surveys. Associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
5
0
2
Order By: Relevance
“…This may be due to the demands of working in a high-volume environment not affording them the opportunity to make certain diagnoses [ 23 ]. However, many of these physicians also have positive attitudes regarding antibiotic use and believe antibiotic administration to be the best course of treatment for their patients [ 24 ]. These findings may assist hospitals in creating effective policies to reduce unnecessary antibiotic prescription, which can lead to adverse events and the proliferation of drug-resistant microorganisms [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the demands of working in a high-volume environment not affording them the opportunity to make certain diagnoses [ 23 ]. However, many of these physicians also have positive attitudes regarding antibiotic use and believe antibiotic administration to be the best course of treatment for their patients [ 24 ]. These findings may assist hospitals in creating effective policies to reduce unnecessary antibiotic prescription, which can lead to adverse events and the proliferation of drug-resistant microorganisms [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study found that pre-intervention antibiotic prescription rates were high, above the NMCS standards for both acute diarrhoea and acute URI, and that they reduced significantly in the post-intervention period to below the NMCS standards. Previous studies have identified various factors related to high rates of antibiotic prescribing, which include regulation and enforcement laxity, diagnostic uncertainty, perceived demand and patient expectations, practice sustainability and financial considerations, influence from medical representatives and inadequate knowledge (16, 17). Patient expectations and pressure from parents have an enormous influence on physicians’ antibiotic prescribing habits (18, 19).…”
Section: Discussionmentioning
confidence: 99%
“…Muitos autores questionam a prescrição de antibióticos em certas situaç ões clínicas, como as que se presumem ser infeç ões de origem viral 7,27,28 . Também Medeiros et al 21 , num estudo realizado no Algarve, Canhota 29 , num estudo realizado na Região de Saúde de Lisboa, e Caldeira et al 16 , num estudo realizado a nível nacional, sugerem a utilização excessiva e inadequada de antibacterianos, provavelmente em situaç ões em que não é provável a existência de infeção bacteriana (infeção respiratória alta e gripe).…”
Section: Indicações Que Motivaram a Prescrição De Antibióticosunclassified
“…Melhorar as ferramentas de diagnóstico é um dos passos mais importantes para reduzir o uso de antibióticos nas infeç ões virais e limitar o uso de antibióticos de largo espetro 5 . Além do dilema do diagnóstico, muitos outros fatores influenciam a forma como os antibióticos são prescritos, nomeadamente as questões culturais, a perceção dos médicos sobre as expetativas dos doentes, a formação e o conhecimento dos profissionais de saúde, o acesso à informação, o desconhecimento do padrão de resistência bacteriana local, os incentivos económicos e o marketing farmacêutico 1,6,7 . O receio de maus resultados clínicos e do risco de complicaç ões e de eventuais consequências pode conduzir também à prescrição excessiva ou à prescrição de medicamentos inapropriados ou mais dispendiosos 8 .…”
Section: Introductionunclassified